Survey on Trends, Challenges, and Opportunities of Honey Production and its Marketing System in Hawa Gelan District Kellam Wollega Zone Western Ethiopia - Yue, Liangwen; Wu, Chunyou; Zhang, Mier; Huang, Qiushuang (Journal of Theory and Practice of Management Science, 2024)
The study was conducted in Hawa Gelan District, Kellem Wollega of Western Oromia national regional state, Ethiopia to assess trends, challenges and opportunities of honeybee production and marketing systems. Structured questionnaire was employed for the study. The cross-sectional study design were carried out by using desk research, interviews, surveys and visual observation as methods in seeking answer to research questions. Purposive (district), simple random (Peasant Associations) and Census (beekeepers) sampling techniques were employed to select 96 beekeepers from two Peasant Associations. The collected data were analyzed by using SPSS version 20. In the study area, three types of honeybee production practices were identified, namely: Traditional, Intermediate and Movable frame hive honeybee production practices. The result shows most 69.79 % of beekeepers in the study area have owned only traditional bee hives. As a result the average annual honey produced per households was very low which estimated 93 kg in 2015. The average amount of honey harvested /hive/year from traditional hive, transitional hive and modern hive were 4.32±0.042kg, 9.83±1.05kg and 14.2±2.52kg respectively. The mean yields obtained from the three hives were statistically significant at (p < 0.05). From the beekeepers (64.6%) and (59.3%) have declared that deceasing trend of honey production and colony number from time to time respectively. Honey marketing participants were consumers (35%), retailers and consumers (31%), retailers (24%) and collectors (7.5%). The most important constraints, as beekeepers responded in their order of sequence were pests and predators (41.30%), poisoning of agro-chemicals (23.60%), high cost of modern hives and accessories (11.20%), shortage of bee forages (9.40%), low quality of honey products (7.20%), Poor infrastructure development (5.30%) and other factors (2.0%) were identified respectively. Despite of these, there are also future opportunities like presence of huge number of bee colonies (32.5%), availability of diverse vegetation plants and ample sources of water (21.70%), increasing demand of local honey (17.65%), presence of good government policy (9.0%) and others factors (19.15%). Further study is required to characterize honey bees of the area, quality of honey, major pests, predators and disease of economic importance. However, improving honey bee production techniques is important.